2019
DOI: 10.1021/acs.inorgchem.9b01335
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Design of Near-Infrared Al3+ Fluorescent Probes Based on Salicylaldehyde Acylhydrazone Schiff Base Derivatives

Abstract: The aim of this paper is to design near-infrared (NIR) Al3+ fluorescent probes based on a Schiff base to extend their applications in biological systems. By combining benzo­[h]­quinoline unit and salicylaldehyde acylhydrazone, we designed two new Schiff base derivatives. According to theoretical simulations on previous experimental Al3+ probes, we obtained the appropriate theoretical approaches to describe the properties of these fluorescent probes. By employing such approaches on our newly designed molecules,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…According to the titration data mentioned above, it was found that the emission intensity of BHMMP was linearly related to the Al 3+ concentration, in the range of 1.0-10.0 µM (R 2 = 0.9908), which indicated that BHMMP could be successfully used as a quantitative tool to evaluate Al 3+ (Figure S1). The detection limit (LOD) was obtained from the result of fluorescence titration as 7.04 × 10 −7 M (3σ/S, where σ is the standard deviation of the blank solution, and S is slope from plotting the fluorescence intensity versus the concentration of Al 3+ ), which was below the guideline value of Al 3+ in drinking water prescribed by WHO (the maximum concentration was 7.4 µM) [55,56]. Fluorescence titration experiments were performed to study the quantitative fluorescence sensing ability of BHMMP to Al 3+ .…”
Section: Fluorescence and Uv-vis Spectral Response Of Bhmmp To Al 3+mentioning
confidence: 99%
“…According to the titration data mentioned above, it was found that the emission intensity of BHMMP was linearly related to the Al 3+ concentration, in the range of 1.0-10.0 µM (R 2 = 0.9908), which indicated that BHMMP could be successfully used as a quantitative tool to evaluate Al 3+ (Figure S1). The detection limit (LOD) was obtained from the result of fluorescence titration as 7.04 × 10 −7 M (3σ/S, where σ is the standard deviation of the blank solution, and S is slope from plotting the fluorescence intensity versus the concentration of Al 3+ ), which was below the guideline value of Al 3+ in drinking water prescribed by WHO (the maximum concentration was 7.4 µM) [55,56]. Fluorescence titration experiments were performed to study the quantitative fluorescence sensing ability of BHMMP to Al 3+ .…”
Section: Fluorescence and Uv-vis Spectral Response Of Bhmmp To Al 3+mentioning
confidence: 99%
“…40,41 The phenol group in phenol-based Schiff base units is deprotonated in the coordination process, which could diminish the electrondonating ability of the oxygen atom. [42][43][44][45][46] Moreover, it has been reported that the uorescence signal of hemicyanine-based NIR uorophores could be turned in a controllable manner by diminishing the electron-donating ability of the oxygen atom in its phenol group. Therefore, a hemicyanine-based NIR uorescent probe using salicylidene acylhydrazone Schiff bases as a selective recognition group has great potential in the selective recognition of Cu 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the flexibility and variability of Schiff bases in terms of structure and physical and chemical properties, it has become an attractive research object. [ 1,2 ] Schiff bases form metal complexes with various structures under certain conditions, [ 3–5 ] and these complexes have distinguished roles in photovoltaic materials, [ 6 ] magnetism, [ 7 ] nanomaterial catalysts, [ 8,9 ] capture performance, [ 10 ] nonlinear optical properties, [ 11 ] chemical sensors, [ 12,13 ] fluorescent materials, [ 14 ] and antiviral activity and other fields. [ 15,16 ] Quinazoline has the skeleton of a variety of alkaloids, its derivatives have multiple biological activities and show unusual high affinity for metal ions, also form all kinds of coordination compounds with many transition metals.…”
Section: Introductionmentioning
confidence: 99%